Tracheal Squamous Cell Carcinoma Treated with Tracheal Resection and Anastomosis in a Cat - Zachary A. Miller; Sheldon Padgett; Alex Terreros; Emily Pearce (Case Reports in Veterinary Medicine)
A 10-year-old male castrated domestic shorthair cat presented for a suspected tracheal mass. Radiographs confirmed an intraluminal tracheal mass. Tracheal resection and anastomosis of 5 tracheal rings was performed with minimal, mild intraoperative complications and no postoperative complications. Histopathology of the tracheal mass revealed a diagnosis of squamous cell carcinoma (SCC) with incomplete margins both cranially and caudally. Further treatment, including surgical revision, radiation therapy, or chemotherapy, was recommended. At the time of publication, no further treatment has been initiated, and a scheduled consultation with the oncologist has been canceled. The cat is doing well at home with no reported signs of recurrence 120 days postoperatively. This is the first report of a cat with a tracheal SCC to be treated with a tracheal resection and anastomosis and only the third feline tracheal SCC to be treated in the veterinary literature.